2021
DOI: 10.3389/fvets.2021.644967
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and Lipidomic Approaches to Evaluate the Effects of Eucommia ulmoides Leaves on Milk Quality and Biochemical Properties

Abstract: Eucommia ulmoides leaves (EUL) contain a variety of natural bioactive compounds including chlorogenic acid, geniposide acid, and aucubin. These bioactive chemicals improve immune function and regulate lipid metabolism. The aim of this study was to investigate the effects of EUL on the biochemical properties of milk. Twenty Holstein dairy cows were randomly allocated to two groups fed a control (CTR, diet without EUL, n = 10) or EUL (diet containing 3% EUL, dry matter, n = 10) diet for 55 d. At the end of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, cows consuming the RG diet had a greater content of 2,6 dihydroxybenzoic acid which is an anti-oxidant with the potential to have beneficial health effects [ 63 , 64 ] and 2-hydroxyhippurate which has been associated with chemoprevention [ 65 ], thus indicating both diets have the potential to provide beneficial compounds for animal health. The differences observed in the metabolomic profile in this study and others indicates [ 66 , 67 , 68 ] the possibility to alter the nutraceutical value of the final product and thus presents an opportunity for designing dietary strategies for ruminants to potentially target health outcomes for the final consumer.…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, cows consuming the RG diet had a greater content of 2,6 dihydroxybenzoic acid which is an anti-oxidant with the potential to have beneficial health effects [ 63 , 64 ] and 2-hydroxyhippurate which has been associated with chemoprevention [ 65 ], thus indicating both diets have the potential to provide beneficial compounds for animal health. The differences observed in the metabolomic profile in this study and others indicates [ 66 , 67 , 68 ] the possibility to alter the nutraceutical value of the final product and thus presents an opportunity for designing dietary strategies for ruminants to potentially target health outcomes for the final consumer.…”
Section: Discussionmentioning
confidence: 67%
“…It has been reported that iridoids, flavonoids, phenylpropanoids, and other substances in Eucommia ulmoides have antioxidant, anti-inflammatory, and immunity effects [ 28 , 54 , 55 ]. In addition, chlorogenic acid [ 36 , 37 ], quercetin [ 38 ], and rutin [ 56 ] increase immune and antioxidant capacity and promote animal growth and development. It was shown that EUE contained abundant chlorogenic acid, galangal, woodruff nucleoside acid, peach leaf coral glycosides, rutin, and quercetin, which may improve the immune function and growth performance of chicks, indicating EUE can be a potential feed additive.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid, flavonoid, and rutin in Eucommia ulmoides have an obvious effect of promoting growth [ 33 , 34 , 35 ]. Chlorogenic acid, flavonoid, and quercetin have an antioxidant effect [ 36 , 37 , 38 , 39 ]. Furthermore, flavonoids can improve the immune ability of the body [ 40 ].…”
Section: Introductionmentioning
confidence: 99%